Implant Survival of Constrained Acetabular Device in Primary Total Hip Arthroplasty Based on Data From the Finnish Arthroplasty Register - Mikko Karvonen; Inari Laaksonen; Pekka Pulkkinen; Antti Eskelinen; Jaason Haapakoski; Ari-Pekka Puhto; Jukka Kettunen; Mikko Manninen; Keijo T. Mäkelä (Elsevier, 2022)
Background: Constrained acetabular devices were developed to prevent dislocations after total hip arthroplasty (THA). However, the data on their success have been contradictory. In this study, we aimed to assess implant survival of the constrained acetabular device in primary THA based on the Finnish Arthroplasty Register data.Methods: A total of 373 primary THAs with constrained acetabular devices inserted from 2006 to 2017 were included. A reference group was formed on a 1:3 basis and matched for age, sex, and diagnosis, consisting of 1118 conventional THAs. Implant survival estimates using death as a competing risk were assessed with revision for any reason and for any aseptic reason as the endpoints. The Cox multiple regression models were adjusted for age, sex, and diagnosis. The mean follow-up time was 3.3 (0-12.4) years for the constrained device group and 3.8 (0-12.0) years for the reference group.Results: Overall, there were 21 revisions in the constrained device group and 49 in the reference group. The 8-year survivorship for any reason was 94% (confidence interval [CI]: 91-96) for the constrained device group and 93% (CI: 89-97) for the reference group. With revision for any aseptic reason as the endpoint, the 8-year survivorships were 97% (CI: 95-99) and 94% (CI: 90-98), respectively. During the first 1.5 years, the constrained acetabular device group had a similar revision risk (hazard ratio: 1.09 [CI: 0.57-2.07], P = .8) to that of the reference group.Conclusion: The constrained acetabular device had good survival in primary THA, and our results support its continued use even in high-risk patients.